The local vicinity of spin sums for certain mass-dimension-one spinors - Bueno Rogerio, R. J. [UNESP]; Hoff da Silva, J. M. [UNESP] (Epl Association, European Physical Society, 2017)
The usual formulations of Elko is well known to lead to a subtle Lorentz symmetry breaking encoded in the spin sums. Recently it was proposed a redefinition in the dual structure, along with a given mathematical device, which eliminates the Lorentz breaking term in the spin sums. In this work we delve into the analysis of this mathematical device providing a solid framework to the used method. Copyright (C) EPLA, 2017